Thermoregulation mechanisms and perspectives for validating thermal windows in pigs with hypothermia and hyperthermia: An overview - Gómez-Prado, Jocelyn; Pereira, Alfredo M. F.; Wang, Dehua; Villanueva-García, Dina; Domínguez-Oliva, Adriana; Mora-Medina, Patricia; Hernández-Avalos, Ismael; Martínez-Burnes, Julio; Casas-Alvarado, Alejandro; Olmos-Hernández, Adriana; Ramírez-Necoechea, Ramiro; Verduzco-Mendoza, Antonio; et al. (Frontiers in Veterinary Science, 2022)
Specific anatomical characteristics make the porcine species especially sensitive to extreme temperature changes, predisposing them to pathologies and even death due to thermal stress. Interest in improving animal welfare and porcine productivity has led to the development of various lines of research that seek to understand the effect of certain environmental conditions on productivity and the impact of implementing strategies designed to mitigate adverse effects. The non-invasive infrared thermography technique is one of the tools most widely used to carry out these studies, based on detecting changes in microcirculation. However, evaluations using this tool require reliable thermal windows; this can be challenging because several factors can affect the sensitivity and specificity of the regions selected. This review discusses the thermal windows used with domestic pigs and the association of thermal changes in these regions with the thermoregulatory capacity of piglets and hogs.